Ensuring a Certain State of Death in the Sunnah: An Objective Study - Al-Shorman, Khaled Mohamed Mahmoud (Dirasat: Shari'a and Law Sciences, 2021)
This research deals with the issue of ensuiring a specific state of death of a muslim in light of the Sunnah. The research in its sources is based on the Sunnah of the Prophet, may God’s prayers and peace be upon him, based on what was mentioned in the Holy Qur’an, and the sayings and actions of the honorable Companions, may God be pleased with them. The research consists of two sections. The first consists of the definition of eagerness for a specific state of death, the legitimacy of being anxious for a specific state of death, and the relationship of eagerness for a specific state of death to predestination. The second topic deals with the legitimate reasons for being anxious about a specific state of death, and the manifestations of being anxious about the specific state of death. The study found that there are legitimate reasons to be anxious for a specific state of death, such as the hope of burial in the virtuous spot, or death in the virtuous state, or deliverance from temptation, among others. In addirtion, there are better types that one needs to be careful about, such as death in a virtuous time, a virtuous place, or a virtuous state. Moreover, there is a specific state to identify death as a goal such as sincerity, certainty of God’s grace, continuity of work, supplication of others, good faith in God, and honesty in supplication.